2019
DOI: 10.1039/c9na00256a
|View full text |Cite
|
Sign up to set email alerts
|

Non-ohmic behavior and resistive switching of Au cluster-assembled films beyond the percolation threshold

Abstract: Networks based on nanoscale resistive switching junctions are considered promising for the fabrication of neuromorphic computing architectures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(129 citation statements)
references
References 57 publications
(95 reference statements)
4
125
0
Order By: Relevance
“…dρ/dT > 0. Figure 5a shows that cluster-assembled gold films have a negative TCR, in particular near RT, the oscillation around zero at lower temperatures can be ascribed to the presence of switching events of amplitude smaller than the resistance temperature variations 22,23 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…dρ/dT > 0. Figure 5a shows that cluster-assembled gold films have a negative TCR, in particular near RT, the oscillation around zero at lower temperatures can be ascribed to the presence of switching events of amplitude smaller than the resistance temperature variations 22,23 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to provide further elements to highlight the role of the high density of grain boundaries and defects in determining the conduction regime, we have characterized the behavior of films under constant bias in the time. Since cluster-assembled gold films exhibit resistive switching (RS) phenomena [21][22][23] , the evolution of the RS activity with temperature can provide useful elements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each ionogel sample was then provided with a couple of 150 nm-thick cluster-assembled Au electrodes (in a sandwich geometry) by means of supersonic cluster beam deposition (SCBD) [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Cluster-assembled Au electrodes have a granular structure characterized by a high electrical conductivity typical of gold and a low density of about 8.0 g/cm 3 [ 56 ]. It was already demonstrated that supersonically accelerated Au clusters can partially penetrate and implant into the surface of soft polymeric substrates, leading to a high interfacial area and robust adhesion [ 52 , 57 ], providing an efficient and stable electrolytic double layer at the electrode-ionogel interface.…”
Section: Resultsmentioning
confidence: 99%